ON THE PROSPECTS OF CREATING A SPECIAL LAW OF UKRAINE ON MONEY SECURITY OF MILITARY SERVANTS - Удовенко, О. В. (Київський національний університет імені Тараса Шевченка, 2020)
The article focuses on the substantiation of the need for the creation and adoption of a draft special law of Ukraine on financial support of military personnel, as well as to outline the structure and main content of this draft law. The general provisions of the proposed draft Law define: the object of legal regulation; the scope of the Law application; the concept and the essence of military personnel financial support; the cash support system management; principles, grounds and conditions of cash security; restrictions on the principle of cash security equality; peculiarities of changing the amount of cash collateral; peculiarities of termination and suspension of the right to a monetary allowance. In separate sections, it is proposed to settle the essence, grounds and conditions for the accrual and payment of monthly basic, monthly additional and one-time additional types of cash support, as well as a set of additional guarantees for military personnel cash support. It is substantiated that the creation and adoption of the proposed draft Law of Ukraine will contribute to: a real increase (to an appropriate level) of the social security of military personnel in Ukraine; convergence of national legislation on military service and the legal status of military personnel in the corresponding legislation of the states of the North Atlantic Alliance. This will bring the standards of decent work and social security of professional public servants in Ukraine up to the corresponding standards stipulated in the EU member states, which are also members of the Alliance.

Стаття присвячена обґрунтуванню потреби створення та прийняття проєкту спеціального закону України про грошове забезпечення військовослужбовців, а також окресленню структури та основного змісту цього законопроєкту. В загальних положеннях пропонованого проєкту Закону визначається: об’єкт правового регулювання; сфера застосування Закону; поняття, сутність грошового забезпечення військовослужбовців; управління системою грошового забезпечення; принципи, підстави та умови грошового забезпечення; обмеження принципу рівності грошового забезпечення; особливості зміни розміру грошового забезпечення; особливості припинення та призупинення права на грошове забезпечення. В окремих розділах запропоновано врегульовувати сутність, підстави та умови нарахування та виплати щомісячних основних, щомісячних додаткових та одноразових додаткових видів грошового забезпечення, а також комплекс додаткових гарантій грошового забезпечення військовослужбовців. Обґрунтовується, що створення та прийняття запропонованого проєкту Закону України сприятиме: реальному підвищенню (до належного рівня) соціальної безпеки військовослужбовців в Україні; зближенню національного законодавства про військову службу та правовий статус військовослужбовців до відповідного законодавства держав Північноатлантичного альянсу; наближуватиме стандарти гідної праці та соціальної безпеки професійних публічних службовців в Україні до відповідних стандартів, що передбачені у державах-членах ЄС, котрі також є членами Альянсу
ЩОДО ПЕРСПЕКТИВ СТВОРЕННЯ СПЕЦІАЛЬНОГО ЗАКОНУ УКРАЇНИ ПРО ГРОШОВЕ ЗАБЕЗПЕЧЕННЯ ВІЙСЬКОВОСЛУЖБОВЦІВ
Keywords: military service; military personnel; financial support; wages; employee; legislative reform; військова служба; військовослужбовець; грошове забезпечення; заробітна плата; працівник; реформа законодавства.